Analysis AZF Gene Deletions in Infertile Men in Indonesia - Hanizar, Evi; Hinting, Aucky (UNEJ e-Proceeding, 2014)
Infertile men with the low quantity and quality of sperm associated with gene deletions in the long arm of chromosome Y (YQ), in the region known as the AZF region (Azoospermic Factor). This study aims to analyze the AZF gene deletions in infertile men with abnormal sperm categories ranging oligozoospermia, Oligoasthenoteratozoospermia until azoospermia. This study includes the type of cross-sectional observational study and DNA samples obtained from the blood of primary infertile men. Extraction of DNA uses a DNA extraction kit and DNA amplification uses polymerase chain reaction method. The analysis includes the number, motility and morphology of sperm conducted by WHO standard. Analysis of deletion is determined from the size of the base pairs of DNA amplification product. The results showed the prevalence of deletions in azoospermic category higher than the prevalence in other categories. Sequentially, the prevalence of deletions was followed by a severe category Oligoasthenoteratozoospermia, Oligoasthenoteratozoospermia, severe oligoteratozoospermia and oligoteratozoospermia. The most frequent gene deletions are sY86 gene, followed by sY84, while the most rare gene deletions are DAZ gene / sY255. This is in contrast with previous studies because of the background sample of infertile men from several races in Indonesia, the number of samples and the location of genes analyzed in the sub-region AZF. Deletions involving many genes in the AZF subregion associated with the smaller quantity and quality of sperm. Key Words : male infertility, azoospermic factor, gene deletion, sperm abnormality